Cicatricial pemphigoid rarely involves the scalp. - Ball, S; Walkden, V; Wojnarowska, F (1998)
We present a case of cicatricial pemphigoid with significant scarring alopecia as a major manifestation and review our series of cicatricial pemphigoid patients in Oxford (UK). Only four of 54 patients had scarring alopecia of the scalp. While rare, this manifestation poses a difficult management problem; patients find this cosmetically distressing and there are no successful treatments available to date.